Statistical Investigation of Extraction Parameters of Keratin from Chicken Feather using Design-Expert - Nuruldiyanah, Kamarudin; Sharma, Swati; Chua, Gek Kee; Syed Mohd Saufi, Tuan Chik; Ritu, Gupta (Springer Berlin Heidelberg, 2017)
Uncontrolled disposal of feathers from the poultry industry and slaughterhouses is environmentally undesirable. The feathers are composed of approximately 90% of keratin which is an important ingredient of cosmetics, shampoos and hair treatment creams. This study aimed to determine the optimum conditions for the extraction of keratin from chicken feathers. The extraction of keratin using various reducing agents was studied using statistical experimental design. In the extraction process, pH, temperature, ratio of reducing agents, mass of chicken feathers and incubation time were analyzed. The keratin in the total extracted protein was purified by size exclusion chromatography, sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) and further characterized using amino acids profile analysis. The surface morphology and chemical composition were studied by scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR) analysis. Sodium sulfide (Na2S) yielded 84.5% of keratin as compared to sodium hydroxide (43.8), urea mixture (50.6), mixture of sodium dodecyl sulfate (SDS) and sodium bisulfite (18.3) and a mixture of Na2S and sodium hydroxide (41.5%) under optimized conditions. The optimum yield of keratin was achieved at 80.9 °C in 9.5 h with 0.05 M sodium sulfide using response surface methodology (RSM). Among the five parameters screened, pH was found not to be significant because the p value was greater than 0.05.